O Uso de operações linguístico-discursivas da crítica genética na reescritura de textos - Bezerra, Lidiane de Morais Diógenes (2013)
As a professor in Curso de Licenciatura em Letras, from Campus Avançado Profa Maria Eliza Albuquerque Maia (CAMEAM),do Estado do Estado do Rio Grande do Norte (UERN), in the town of Pau do Ferros, in the state of Rio Grande do Norte, we had the chance to carry out several writing activities , as well as guiding re-writing activities for the texts produced. From this experience, we started looking at the need of reflecting upon the writing process in higher education. Thus, we aim at analyzing, in this research, the methodology used in the moment of carrying out the writing practices activities in higher education, investigating, in particular, the rewriting practices, concerning the operations used for carrying out such activities, as well as the sense effects produced from the alterations which were made in the texts. Our theoretical foundation is grounded on a conception of text as a verbal action , what reveals a socio-interactional view of the language (MARCUSCHI, 2008; SAUTCHUK, 2003). As the production of written texts, our research focus, we assume that, for this activity, we deal with distinct figures (active writer and internal reader), so that we can, apart from writing, reflecting upon our writing and, this way, deciding about operations which are carried out to make the alterations which are necessary to the rewriting of our texts (SAUTCHUK, 2003). Still about the theoretical foundations used in this research, we made use of the theories from the Textual Analysis of Discourse (TAD) which discusses the belief on the evidence on the existence of the texts, which is opposite to the fixist view of textuality which believes that the texts exist by themselves. (ADAM, 2008; [2005]2010). Under this perspective, we have also adopted, the concepts which come from genetics criticism which is concerned about the relation between text and genesis, using as objects documents which bring traits of the text in progress, on the ground that the text is the result of work in progress, and the writing practice, on the other hand, as an activity in a continuous movement (HAY, [1975]2002; DE BIASI, [2000]2010; GRÉSILLON, 1989; [1990]2008; [1992]2002; SALLES, 2008a). The methodology in this research is an ethnography-based one, an approach which focuses on the process, as well as is meaning-based. To understand the objectives proposed in our research, we made use of different procedures of collecting data which include an ethnographic study, such as: observation, note-taking, document analysis. The data which were analyzed were collected during the semester of 2008.2, in a first term classroom of Curso de Letras from CAMEAM, when we were able to collect twenty-one written texts and all of them were rewritten based on rewriting activities, what provides a corpus of forty-two texts which will be analyzed based on the linguistics operations identified by Generative Grammar and adopted by Lebrave and Grésillon (2009). From these analyses, we were able to confirm that writing is a process, and rewriting has become an extremely important activity for this process. Still due to these data, we observed that substitution was the most used operation by text authors. We believe that this result is justified by the fact that the substitution, according to what proposes the Genetic Criticism, constitutes the source of all erasure, from which one can easily make a change in writing. Regarding the operations of addition and deletion, we found that they were used in quantitative terms, almost equivalently, which can be explained when we see that the two operations require, by the author of the text, different strategies from those used for the replacement, what includes , respectively, adding or removing a segment. Finally, we found out that the shift operation was the least used, since it works with a segment that will not be replaced, added or deleted, but transferred to another place of text, which requires a greater ability of the author to perform this operation and not compromising the meaning of his/her writing. As a result, we hope to contribute to the reflection on the teaching of writing, considering, in a particular way, those with a Bachelor in Arts. Our analysis will contribute to the teaching of Portuguese language, specifically for activities that guide the production of texts in order to explore with students the ability to rewrite their own text